2020
DOI: 10.3389/fimmu.2020.00864
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Inflammatory Signatures in Peripheral Blood and Bronchoalveolar Cells Reveal Compartment-Specific Effects of HIV Infection

Abstract: The mechanisms by which HIV increases susceptibility to tuberculosis and other respiratory infections are incompletely understood. We used transcriptomics of paired whole bronchoalveolar lavage cells (BLCs) and peripheral blood mononuclear cells to compare the effect of HIV at the lung mucosal surface and in peripheral blood. The majority of HIV-induced differentially expressed genes (DEGs) were specific to either the peripheral or lung mucosa compartments (1,307/1,404, 93%). Type I interferon signaling was th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…The presence of HIV in the lung is likely to contribute to immunopathology and immune dysfunction, increasing susceptibility to respiratory diseases. We report a greater number of lymphocytes in HIV-infected airways, as has previously been described as lymphocytic alveolitis, thought to be predominantly made up of cytotoxic CD8+ T cells (24,26,27,37). On its own, lymphocytic alveolitis causes limited pathology (25), but may contribute to the increased prevalence of pulmonary disease during HIV infection.…”
Section: Discussionmentioning
confidence: 50%
“…The presence of HIV in the lung is likely to contribute to immunopathology and immune dysfunction, increasing susceptibility to respiratory diseases. We report a greater number of lymphocytes in HIV-infected airways, as has previously been described as lymphocytic alveolitis, thought to be predominantly made up of cytotoxic CD8+ T cells (24,26,27,37). On its own, lymphocytic alveolitis causes limited pathology (25), but may contribute to the increased prevalence of pulmonary disease during HIV infection.…”
Section: Discussionmentioning
confidence: 50%
“…This suggested that HIV-infected individuals had increased BAL CD8 T cells but smoking suppressed this effect. Increased BAL CD8 T cells in HIV-infected individuals have been observed in prior studies including cART naïve HIV-infected subjects (8) and also in HIV-infected individuals started on cART (9). Few studies have focused on HIV-infected individuals on established ART with viral suppression, which was uniquely addressed in this study.…”
mentioning
confidence: 81%
“…(10) Despite the cavitation that may increase the risk of TB recurrence, human immunodeficiency virus (HIV) coinfection is one of the most important risk factors associated with TB recurrence due to loss or dysfunction of immunity and several other poorly understood mechanisms for immunopathogenesis. (11)(12)(13) TB and HIV has bidirectional impact; TB infection among HIV patient cause slowing CD4 recovery and increasing progression to AIDS; in the other hand HIV infection among TB patient also increase TB disease progression. ( 14) It is estimated that 1.2 million people has died from TB globally, and among these, 17% is HIV infected.…”
Section: Introductionmentioning
confidence: 99%